Community participation in decentralized management of natural resources in the southern region of Mali - Umutoni, Clarisse; Ayantunde, Augustine A.; Turner, M.; Sawadogo, G.J. (Canadian Center of Science and Education, 2016)
Decentralized governance of natural resources is considered one of the key strategies for promoting sustainable management of natural resources at local level. Effective decentralized natural resource management requires strong local natural resource institutions. Therefore, strengthening local institutions governing the management of natural resources is one of the core principles of decentralization reforms in Francophone West Africa countries. This study assessed the existing local institutions (rules, norms and or local conventions) governing the management of natural resources and forms of community participation in the development of these natural resource institutions. Our findings showed significant variation within the study sites regarding the level of knowledge of existing local rules and norms governing the management of natural resources by the respondents. Results showed that the level of knowledge of local conventions was significantly (P < 0.05) higher in the district of Bougouni than in the district of Koutiala (a score of 3.16 compared to 1.70 on a scale of 0 to 4).This study shows also that participation was dominated by a small group of individuals, often community leaders and elites. The results suggest that women are marginalized. Presently, the big challenge that faces the institutions governing natural resource use in the study area is the system of representativeness in the community in the development of local rules and norms as community leaders and household heads often dominate, which does not encourage active participation of community members. Therefore, for effective implementation of local natural resource institutions, the interest of key natural resource users should be taken into account. It is also important to promote rules and norms that attempt to protect or strengthen women’s access to natural resources in the community.